The Development of Scratch-Based Interactive Mathematics Learning Media to Enhance Understanding of Exponents - Lia Arista; Dadan Dasari; Eyus Sudihartinih; Kakoma Luneta (FKIP Universitas Lampung, 2026)
This study addresses the need for interactive mathematics learning media to improve students' understanding of the concept of exponents. The objective of this research is to develop and evaluate Scratch-based learning media using the ADDIE model. This study employed a Research and Development (R&D) method consisting of five stages: analysis, design, development, implementation, and evaluation. Data were collected through expert-validation questionnaires, User Acceptance Test (UAT) questionnaires, and conceptual-understanding tests administered before and after the implementation of the media. The validation results indicated that the developed media and learning materials were highly valid, with validity scores of 0.90 and 0.95, respectively. In addition, the conceptual understanding test instrument was validated by a mathematics education expert and was deemed suitable for assessing students' understanding of exponent concepts. The User Acceptance Test (UAT) was conducted with prospective mathematics teachers to evaluate the usability and practicality of the developed media. In contrast, the implementation and learning outcome assessments were conducted with students. The UAT results showed that the developed media was positively evaluated by users, obtaining a score of 82.9%, which falls within the very good category. The developed media provided interactive learning activities that encouraged students to actively engage with concepts of exponents throughout the learning process. The results showed that students achieved better learning outcomes, as evidenced by increases in their pretest and posttest scores. The average N-Gain score of 0.84 was categorized as high, indicating an improvement in students' understanding of exponent concepts after using the developed media. The study resulted in a Scratch-based multimedia learning media that was evaluated as highly valid and positively received by users. The findings indicated improvements in students' understanding of exponent concepts, while several usability aspects, particularly related to device compatibility, may be further refined in future development. Keywords: ADDIE, exponent, learning media, Scratch.